Supply Chain Analysis Of Brown Sugar Commodity In Kendari City Southeast Sulawesi - Dwi Rahmawati Rasyid; Weka Gusmiarty Abdullah; Samsul Alam Fyka (International Journal of Technology and Education Research, 2025)
This research aims to determine the supply chain flow of brown sugar commodities in Kendari City. This research was conducted in Kendari City, which was chosen deliberately with the consideration that Kendari City is one of the marketing centers for palm sugar, but the community does not process palm sap into brown sugar, so it was felt that a supply chain was needed to understand the flow of goods, information flow and financial flow of brown sugar commodity in Kendari City. This research was carried out in June 2023 until completion. The population in this study was 15 people. The data collection technique used was the snowball sampling technique, starting from retailers, and collectors to brown sugar processors. Research data was analyzed descriptively and qualitatively. The results of the research show that: 1) The supply chain flow for brown sugar in Kendari City originates from Penanggosi Village, East Kolaka 2) The flow of goods consists of Brown Sugar Processors - Collectors - Retailers - Consumers 3) The flow of information that occurs is well integrated 4) Flow finances flow from Consumers - Retailers - Collectors - Brown Sugar Processors.